2021
DOI: 10.3390/act10120312
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Energy Harvesting: A Systematic Review of Reviews

Abstract: In the last decade, an enormous amount of attention has been paid to piezoelectric harvesters due to their flexibility in design and the increasing need for small-scale energy generation. As a result, various energy review papers have been presented by many researchers to cover different aspects of piezoelectric-based energy harvesting, including piezo-materials, modeling approaches, and design points for various applications. Most of these papers have tried to shed light on recent progress in related interdis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 80 publications
0
7
0
1
Order By: Relevance
“…관련 기술중 압전 및 마찰전기 효과를 사용한 에너지 하베스팅에 대한 연구가 최근 활발하게 진행되고 있다. 압전 [1][2][3][4][5][6] 및 마찰 전기 [7][8][9][10][11] [12][13][14][15] 가 있는데 세계적으로 납사용을 규제하면서 최근에는 BaTiO 3 (BTO), 16,17) ZnO 18) 및 PVDF (polyvinylidene difluoride)…”
Section: 서 론unclassified
“…관련 기술중 압전 및 마찰전기 효과를 사용한 에너지 하베스팅에 대한 연구가 최근 활발하게 진행되고 있다. 압전 [1][2][3][4][5][6] 및 마찰 전기 [7][8][9][10][11] [12][13][14][15] 가 있는데 세계적으로 납사용을 규제하면서 최근에는 BaTiO 3 (BTO), 16,17) ZnO 18) 및 PVDF (polyvinylidene difluoride)…”
Section: 서 론unclassified
“…The cymbal and bridge are the most common designs for piezoelectric harvesters [23]. Ceramic piezoelectric transducers are relatively fragile; in fact, they can be destroyed when exposed to energy produced from human motions [24,25]. Nowadays, there are different structures of piezoelectric generators; in particular, they are classified into two categories:…”
Section: Piezoelectric-based Smart Floor Solutions: Working Principle...mentioning
confidence: 99%
“…Therefore, vibration-frequency-increasing piezoelectric wave energy converters (pWECs) have become a popular topic recently [23,24]. A comprehensive review of the state-of-the-art research on pWECs can be found in [25,26]. Mechanical contacts and magnetic impacts are commonly used vibration-frequency-increasing conversion techniques for piezoelectric cantilever beams.…”
Section: Introductionmentioning
confidence: 99%